Level of Implementation of PNP Oplan Double Barrel in the Province of Camarines Sur: Basis in Formulating a Holistic Rehabilitation Program for Drug Surrenderees - Tanjay, Lorlie (JPAIR Multidisciplinary Research, 2020)
In support of the Barangay Drug Clearing strategy of the Philippines, the Oplan Double Barrel program was implemented under PNP Command Memorandum Circular No. 16- 2016. The program impacted almost all sectors of the community, especially the drug surrenderees. This quantitative descriptive research evaluated the level of implementation of PNP Oplan Tokhang in the province of Camarines Sur. It determined the effectiveness of intervention strategies towards the rehabilitation of the drug surrenderees. A survey questionnaire was administered to six hundred twenty-four (624) respondents, and it was collected, analyzed, and interpreted using weighted arithmetic mean Kruskal Wallis H and Mann Whitney U test to compare the response. Data revealed that three (3) phases of Oplan Tokhang were effectively implemented. However, the problem with the scarcity of financial resources to provide health and other social services, insufficient rehabilitation personnel, and limited rehabilitation facilities are encountered. Hence, the government should increase budget allocation for the rehabilitation services and strengthened the holistic community-based rehabilitation towards effective oplan tokhang.
Keywords: social science; oplan tokhang; weighted mean; escriptive-quantitative design; Camarines Sur; Philippine